Zoom-Based TOEFL Training Based on Students' Perceptions - Rahmatika Kayyis; Dian Pratiwi (ELT-Lectura, 2021)
TOEFL is a need for college students to continue their study at a well-known university and need to acquire a bachelor's degree. However, COVID-19 led to a primary catastrophe that hit most countries in the world. The implementation of social distancing or distance restrictions imposed by the government has made training and learning carried out, one of which is the usage of an internet interface software solution. This study aims to determine students' perceptions of the application of Zoom-based TOEFL training. Descriptive research by giving online-interview to 44 students who took part in the TOEFL training organized by Language Institute of Business Economics Faculty, University of Muhammadiyah Pringsewu. The positive perception of this Zoom-based TOEFL training is the flexibility, the students can manage to do different activities whilst still join in it. The negative perceptions or weaknesses are the ineffective training time, the network disruption, and the different way in explanation.